Flood Detector Emergency Warning System (International Journal of Engineering and Computer Science, 2013)
Floods occur most commonly when water from heavy rainfall, from melting ice and snow in the country that having cold weather, or from a combination of these exceeds the carrying capacity of the river system, lake, or ocean into which it runs. Due to the effect, many study been conducted as to get ready with a system to alarm people from this disaster. The objective of this project is to match the software (Visual Basic.6) with the system, design the circuit and create a programming code using the Peripheral Interface Controller (PIC) 16F877A microcontroller and apply the GSM Mobile in transmitting the data from one place to another place. Result showed, data was finally sent via Global System for Mobile Communications (GSM) mobile, where it was act as a modem for the system. All three level sensors were also detected the water level. The data from sensor and PIC also were appeared at the control centre. This project can be improved with upgrading the component in Graphical User Interface (GUI) with more function button to make sure it will be more friendly user and interesting. The system is proposed to have the GSM modem will be as a transmission modem in order to have larger coverage, thus it also easily connected to the computer